Chapter 6 Eros and objectivisation - Heinrich, Falk (Taylor & Francis, 2023)
Chapter 6, Eros and objectivisation, takes its point of departure in tango's image as a sensual and erotic dance. Plato argues in various works that carnal eros (desire) must be transcended and transformed into the recognition of eternal beauty. He grounds the realisation of beauty in representations elicited by our visual sense and cognitive capabilities. Dancing is intrinsically somatic and sensory. This chapter devises a theory of beauty experiences that builds upon our embodied desires by proposing that the dynamic relationship between agency and patiency opens up an experience of the transcendence of the (agential) subject. This is possible when the dancer feels that they are danced by the dance proper, affording a simple awareness of movement while moving. The chapter also examines the importance of music for the formation and dissolution of the dancing agent. The chapter concludes that a beautiful experience of dancing must be understood as a somatic awareness that is, in equal measures, an awareness of action and in action. A pleasurable awareness of the flow of interaction reenters the interaction as an integral part of it.